2015
DOI: 10.1007/s11412-015-9224-0
|View full text |Cite
|
Sign up to set email alerts
|

Role taking and knowledge building in a blended university course

Abstract: Role taking is an established approach for promoting social cognition. Playing a specific role within a group could lead students to exercise collective cognitive responsibility for collaborative knowledge building. Two studies explored the relationship of role taking to participation in a blended university course. Students participated in the same knowledge-building activity over three consecutive, five-week modules and enacted four roles designed in alignment with knowledge building pedagogy (Scardamalia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 41 publications
1
23
0
1
Order By: Relevance
“…A role can also be a statement of properties, such as the leader of a group. In CSCL, a role might refer to one's social role in the knowledge building [36]. Conversely, a network role is defined exactly by the associations of the relations a node possesses, and the role might not have a simple linguistic label.…”
Section: Analysing Online Discussionmentioning
confidence: 99%
“…A role can also be a statement of properties, such as the leader of a group. In CSCL, a role might refer to one's social role in the knowledge building [36]. Conversely, a network role is defined exactly by the associations of the relations a node possesses, and the role might not have a simple linguistic label.…”
Section: Analysing Online Discussionmentioning
confidence: 99%
“…In conclusion, despite the limitations of the study that do not allow any generalization of the results -first of all considering the small number of participants and the not-experimental method here adopted -, we were however able to grasp some insights about the processes emerging when a role is chosen or assigned. Nevertheless, future developments are needed in the design of the learning activity, such as: engaging the students in a "learning by modelling" (Palincsar & Brown, 1984) experience, envisaging that the members of each group will take turns in the various roles for each module of the course; in this way, each student would experience the effects of and the contents and process skills associated with each role (Cesareni & Cacciamani, 2015;Sansone et al, 2011;Strijbos et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In line with the main socio-constructivist theories (Jonassen, 1994;Pontecorvo et al, 1995;Varisco, 2002) applied to digital environments (Laurillard, 2008;Trentin, 2005;Wenger, 1998), students' interaction needs to be first promoted and then structured according to specific scaffolds. Various studies (Cesareni et al,2015;Delfino et al, 2006;Sansone et al, 2016b;Strijbos et al, 2004;Weinberger et al, 2010) have indeed showed that it is not guaranteed that -when involved in collaborative online contexts -students will effectively participate, by providing valid contributions to the group activities. Effective and significant collaborative learning requires structured interactions drawn around scripts assigned to students.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Additionally, the communicative strategies employed by the social tutor to support participation and membership must be studied. For this aim, a qualitative approach may be used with Content Analysis of posted messages to identify Conversational Functions (Cesareni, Cacciamani & Fujita, ; Wise, Saghafian, & Padmanabhan, ). Employing this kind of analysis, researchers can analyse the social interactions and communicative strategies in order to understand how the social tutor operates in online communities and how this role can encourage students to have more productive interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Cesareni, Cacciamani and Fujita (2016) reported positive effects of role adoptions in online courses; students who assume roles based on collaboration scripts are more active in terms of writing and reading activities in the online environment. In addition, role takers, compared to non-role takers, tend to vary the nature of their contributions using a larger repertoire of Conversational Functions in online interactions.…”
Section: Practitioner Notesmentioning
confidence: 99%